ABORDAGEM TERMINOLÓGICO-DISCURSIVA: PELO RESGATE DA TERMINOLOGIA E DA TERMINOGRAFIA NO ENSINO E NA APRENDIZAGEM DE LÍNGUAS PARA FINS ESPECÍFICOS NO CONTEXTO BRASILEIRO - Nadin, Odair Luiz [UNESP] (UNICAMP. Programa de Pós-Graduação em Linguística Aplicada do Instituto de Estudos da Linguagem (IEL), 2022)
The aim of this text is to present some reflections on a proposal for an approach to Language Teaching and Learning for Specific Purposes, in order to rescue the relevant role of Terminology and Terminography for the learner of this type of teaching. The terminology has as its initial point the 1930s of the 20th century, especially from the doctoral thesis of the Austrian engineer Eugen Wüster. The Teaching of Languages for Specific Purposes, in turn, emerged three decades later together with the Communicative Approach and is established itself in the second half of the 20th century in the movement called English for Specific Purpose. In this first phase, the relationship between the two areas was quite explicit, because this teaching modality was centered on the lexical and grammatical record specific to the learner’s area. Through a literature review, such as Cabré (1999, 1993), Barros (2004), Gómez de Enterría (2009), Hutchison and Waters (1987); Aguirre Beltrán (2012), Ramos (2019), Dolz; Noverraz and Schneuwly (2004), we present a proposal, called “Terminological-Discursive Approach (ATD)”, of interdisciplinary character, which starts from the analysis of the learner profile, with needs and uses of the language in specific contexts, in which textual genres that are also specific circulate. Thus, we present some principles of ATD based on concepts such as “use of languages in specialized contexts”; “specialized textual genres” and “communicative-specialized competence”. In this way, we hope to contribute to the “revival” of Terminology and Terminography as sciences that can contribute productively to the Teaching and Learning of Languages for Specific Purposes (EALFE).

O objetivo do presente texto é apresentar algumas reflexões sobre uma proposta de abordagem para o Ensino e a Aprendizagem de Línguas para Fins Específicos, a fim de resgatar o relevante papel da Terminologia e da Terminografia para o aprendiz dessa modalidade de ensino. A Terminologia tem como marco inicial os anos 30 do século XX, sobretudo a partir da tese de doutoramento do engenheiro austríaco Eugen Wüster. O Ensino de Línguas para Fins Específicos, por sua vez, surge três décadas depois juntamente da Abordagem Comunicativa e se firma na segunda metade do século XX no movimento denominado English for Specific Purpose. Nessa primeira fase, a relação entre as duas áreas era bastante explícita, pois essa modalidade de ensino centrava-se no registro léxico e gramatical próprios da área do aprendiz. Apresentamos breve revisão bibliográfica, a exemplo de Cabré (1999, 1993), Barros (2004), Gómez de Enterría (2009), Hutchison e Waters (1987); Aguirre Beltrán (2012), Ramos (2019), Dolz; Noverraz e Schneuwly (2004), SWALES, (2009), a proposta que ora apresentamos, denominada “Abordagem Terminológico-Discursiva (ATD)”, que possui caráter interdisciplinar, e parte da análise do perfil de dado aprendiz, com necessidades e usos da língua em contextos específicos, nos quais circulam gêneros textuais também específicos. Assim, trazemos alguns princípios da ATD alicerçados em conceitos como “uso das línguas em contextos especializados”; “gêneros textuais especializados” e “competência comunicativo-especializada”. Desse modo, esperamos contribuir para o reavivamento da Terminologia e da Terminografia como ciências que podem contribuir de forma produtiva ao Ensino e à Aprendizagem de Línguas para Fins Específicos (EALFE).
TERMINOLOGICAL-DISCURSIVE APPROACH: FOR THE RESCUE OF TERMINOLOGY AND TERMINOGRAPHY IN THE TEACHING AND LEARNING OF LANGUAGES FOR SPECIFIC PURPOSES IN THE BRAZILIAN CONTEXT
Keywords: terminology; terminography; use of languages in specialized contexts; specialized textual genres; communicativespecialized competence; language teaching and learning for specific purposes; terminologia; terminografia; uso das línguas em contextos especializados; gêneros textuais especializados; competência comunicativo-especializada; ensino e aprendizagem de línguas para fins específicos